Lodz Through the Ages. A History of the City, Volume 3, 1914-1945 (Lodz University Press, 2024)
The publication is devoted to the history of Lodz in 1914–1945, a time when the great industrial urban center faced the drama of two world wars and a brief period of reconstruction and development in the independent Republic. The authors offer the reader a journey through time from the 19th century "promised land" to 20th century modernity. This journey, paid for by depopulation, change of national face, material losses and devastation of industry, showed the fortitude and strength of the city and its inhabitants. They not only rebuilt destroyed factories, established their own small family businesses, created their own administration, built schools, kindergartens, temples, sacrificially helped the weakest of the metropolitan community, but also had fun. Here, in the fumes of the constant struggle for existence, eminent artists known not only in Poland but also in the world created. The gehenna of war wiped out this world and a huge number of its inhabitants - Lodz citizens. The main text tells the story of destruction and rebirth, and is supplemented by capsules containing excerpts from valuable sources, biographical and interesting facts and illustrations. Publikacja ukazała się dzięki wsparciu finansowemu Urzędu Miasta Łodzi